Spontaneous coronary artery dissection. Issue 12 (18th November 2005) - Naughton, P; Nolke, L; Veerasingam, D; McCarthy, J
Abstract : Spontaneous coronary artery dissection is a rare cause of myocardial ischaemia or sudden death, predominantly affecting young women with no known risk factors for cardiovascular disease. The case described emphasises the benefit of early diagnosis and the need to individualise management based on patient response to treatment.